Sprague‐Dawley and Fischer Female Rats Differ in Acute Effects of Fluoxetine on Sexual Behavior. (30th October 2012) - Miryala, Chandra Suma J.; Hiegel, Cindy; Uphouse, Lynda
ABSTRACT Introduction. The selective serotonin reuptake inhibitor (SSRI), fluoxetine, leads to sexual dysfunction in a substantial proportion of women. In studies with the Fischer inbred rat, the 5‐HT1A receptor has been implicated in this sexual dysfunction. Whether this association with 5‐HT1A receptors holds for other rat strains is not known. Aim. The effects of acute fluoxetine on sexual behavior in two strains of rats that differ in their response to a 5‐HT1A receptor agonist were examined. Whether the strain difference is comparable in naturally cycling and hormonally primed, ovariectomized rats was determined. Methods. Proestrous rats and ovariectomized rats, hormonally primed with estradiol benzoate and progesterone, were treated with varying doses of fluoxetine. Sexual behavior was examined before and after treatment with the SSRI. Main Outcome Measures. Lordosis to mount ratios, lordosis quality, and proceptive behaviors were quantified. Sprague‐Dawley and Fischer females were compared on each of these measures. The IC50 for inhibition of lordosis behavior was determined. Results. In both the intact and the hormonally primed, ovariectomized model, Sprague‐Dawley females were less sensitive to the effects of fluoxetine on sexual behavior. In both groups, fluoxetine showed dose dependency in behavioral inhibition, but a higher dose was required for Sprague‐Dawley than for Fischer females. Naturally cycling, proestrous rats required a higher dose of fluoxetine than hormonally primed ovariectomized rats to produce significant inhibition of sexual behavior. Thus, the strain difference in the response to fluoxetine does not parallel strain differences in the response to a 5‐HT1A receptor agonist. Conclusions. Acute treatment with fluoxetine inhibits lordosis behavior in both Fischer and Sprague‐Dawley females and the strain difference cannot be explained by reported strain differences in the response to a 5‐HT1A receptor agonist. Fluoxetine's inhibition of female rat sexual behavior may involve effects of the SSRI in addition to activation of the 5‐HT1A receptor. Miryala CSJ, Hiegel C, and Uphouse L. Sprague‐Dawley and Fischer female rats differ in acute effects of fluoxetine on sexual behavior. J Sex Med **;**:**–**.